Interindividual Variability in the Bioavailability of Gabapentin Enacarbil Extended Release in Healthy Adults: An Analysis of Data From 6 Phase I Studies. Issue 3 (1st June 2022) - Lal, Ritu; Ellenbogen, Aaron; Gidal, Barry
Abstract : Background: The absorption and bioavailability of oral gabapentin are associated with a high degree of interindividual variability. Gabapentin enacarbil, a prodrug of gabapentin, is well absorbed and provides sustained, dose-proportional exposure to gabapentin. The aim of this analysis was to describe the interindividual variability in the bioavailability of gabapentin after gabapentin enacarbil administration in healthy subjects. Methods: Gabapentin pharmacokinetic (PK) parameters after an oral dose of gabapentin enacarbil 1200 mg (2 600-mg tablets) were compared across 6 phase I studies in healthy adults (n = 12 per study). The distribution of bioavailability values was assessed in all studies. Results: The mean PK parameters of gabapentin were consistent across the trials: maximum concentration range: 6.4–7.9 μg/mL, time to maximum concentration range: 5.2–8.2 hours, area under the plasma–concentration curve extrapolated from time 0 to infinity or at steady state range: 70.8–109.4 μg·h/mL, and bioavailability range: 64.8%–82.9%. Overall, the mean bioavailability was 74.1% (SD, 14.1; coefficient of variation, 19.1%). Individual bioavailability across all studies ranged from 42% to 100%. Conclusions: Gabapentin PK after gabapentin enacarbil administration was consistent across studies, with low interindividual variability in bioavailability. Gabapentin enacarbil may provide more consistent and predictable exposure to gabapentin than oral gabapentin formulations.